2019
DOI: 10.1039/c9ra00959k
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, structural characterization, and thermal and biomedical properties of sulfated polysaccharides from razor clamSolen marginatus

Abstract: In this study, some biological activities of sulfated polysaccharides extracted from Solen marginatus flesh were investigated via physicochemical characterization of the crude polysaccharide SM-CP and its deproteinized fraction SM-DP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The absorbance bands at 1330, 1405, and 1595 cm −1 may be due to the vibration due to amide (−CN−), amine (−N−H), and some carbonyl (−CO−) groups . 3739 The increase in the transmittance at the observed characteristic peaks may be attributed to the microwave-induced variation in the –C−H stretching and number of −O−H, −CN−, and −CO− groups in the structure of chitin extracted from the microwave-treated NNR flour. These microwave-induced variations in the structure of chitin may be correlated with those observed in SEM/EDX analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The absorbance bands at 1330, 1405, and 1595 cm −1 may be due to the vibration due to amide (−CN−), amine (−N−H), and some carbonyl (−CO−) groups . 3739 The increase in the transmittance at the observed characteristic peaks may be attributed to the microwave-induced variation in the –C−H stretching and number of −O−H, −CN−, and −CO− groups in the structure of chitin extracted from the microwave-treated NNR flour. These microwave-induced variations in the structure of chitin may be correlated with those observed in SEM/EDX analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Jridi et al [5] reported the highest sulfate content in SPs from head while the lowest content was related SPs from the skin of Bullet tuna. A number studies have stated that the increase of sulfate content in sulfated polysaccharides could enhance its bioactivity [34] , [35] .…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight of all extracted SPs was lower than those reported by Jridi et al [5] , who extracted SPs from Bullet tuna ( Auxis Rochei ) by-products by enzymatic method. Souissi et al [35] extracted SPs from razor clam, Solen marginatus, and reported two major peaks at 1075 kDa and 237.9 kDa for the recovered SPs. It has been reported that the molecular weight of polysaccharides can be dependent on the extraction process, purification techniques, and deproteinization treatment [21] , [35] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first stage was in the temperature range of 33.2~163.6 • C, during which the weight loss rate reached 12.0%. The result might be attributed to the evaporation of the free water and bounding water to the polysaccharides [48][49][50]. The second stage occurred in the temperature range of 163.6~395.3 • C, during which the weight loss was the most serious.…”
Section: Thermal Property Analysismentioning
confidence: 99%